The Prospect of Business Undergraduates’ Intention to Engage in Digital Entrepreneurship: Do Government Initiatives Matter? - Chu May, Amy Yeo; Hui, Eyva Lim Koon (Studia z Polityki Publicznej, 2024)
The synergies between rapid information technology (IT) development and the shifting paradigms of economic transactions have led to the emergence of digital entrepreneurship. This study aims to investigate potential precursors affecting the intention of final-year business students to engage in digital entrepreneurship. This research was examining the IT acceptance among the business students by employing two tailored technology acceptance models based on the theory of planned behavior and theory of reasoned action models. A sample of 302 respondents were analyzed using SPSS and Smart-PLS. The results revealed that fresh graduates’ intentions to engage in digital entrepreneurship were significantly influenced by their own attitudes towards IT. The study also reaffirmed that the dimensions of I. Ajzen’s theory of planned behavior model, including attitude towards IT, perceived usefulness, perceived ease of use, subjective norms except perceived risk have a “direct effect” on undergraduates’ interest in an Internet-based business model. Although the results have contributed to filling the paucity of the empirical research in digital entrepreneurship, particularly in the Asian region, the availability of information technology, government resources and support to affect digital usage and behavior are not to be underestimated.